ASPEK PERILAKU IBU DENGAN KEJADIAN DIARE BALITA - Rosdiana, Rosdiana; Pratami, Intan Monik; Sari, Andi Nur Indah; Arini, Ketut Novia; Werdini, Yoessy Etna (Ensiklopedia of Journal, 2024)
Abstract: Pahandut Health Center is one of the health centers in Palangkaraya City that is still faced with the problem of diarrhea in children under five. Pahandut Health Center has the highest number of diarrhea cases among children under five compared to other health centers in Palangkaraya City. The purpose of this study was to determine the aspects of maternal behavior with the incidence of diarrhea in children under five. The study used quantitative research with cross sectional design. The study was conducted in July 2022 in the working area of Pahandut Health Center. The population is mothers who have toddlers with a sample size of 126 people. The sampling technique used Purposive Sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was a relationship between maternal hand washing behavior (p value: 0.002) and there was no relationship between exclusive breastfeeding (p value: 0.501) to the incidence of diarrhea in toddlers. It is recommended to mothers who have toddlers to be able to apply clean and healthy living behaviors, especially the behavior of washing hands with soap, so that toddlers avoid diarrhea.Keywords: Exclusive breastfeeding, toddler, diarrhea